Classification of wood charcoal in the Syrian market according to the combustion energy and the specific heat (Damascus University Journal of agriculture sciences, 2021)
Wood charcoal is an important source of energy, especially WITH increasing the prices of other energy resources. Forests are the natural sustainable source of timber and the classification of wood charcoal is still commercial and needs to scientific documentation for determining its quality.The results showed that the coal has the highest quality of wood, followed by charcoal, almond and laurel wood. The coal of eucalyptus wood charcoal was characterized by bad quality because of weak tenderness. It seems to be very important to set several slow ignition and the smoke realized during the ignition. Setting controls to determine the quality of the coal in the local market, and what applies to charcoal is could be entirely applicable to dry wood. The aim of this research is to study the combustion energy, specific heat and the virtual properties of most types of wood charcoal found in the Syrian markets in order to classify these types in terms of quality and determine the thermal efficiency of each species. These types include quercus calliprinous, oak, pine, locust, arbutus andrachne, almond, laurel, fig, eucalyptus and some  imported species.
Keywords: wood charcoal; combustion heat; specific heat; phenotype; quercus calliprinous